173 Footfalls echo in the memory. Issue 3 (9th February 2012) - Tobin, W O; Farrell, M; McGuigan, C
Abstract : A 58-year-old woman presented with a 3.5-year history of falls, unsteadiness and a 6-month history of memory loss. Examination revealed a spastic tetraparesis and multi-domain cognitive dysfunction. MRI brain demonstrated periventricular and deep white matter hyperintensities (Abstract 173 figure 1 ). The cervical spinal cord was normal. Her husband died 1 year previously following a 3-year history of memory loss and limb spasticity. Subsequent questioning revealed husband and wife to be consanguineous. Genetic testing identified husband and wife as being heterozygous for the Glu280Gly (g.50024A→G) mutation in the Presenilin-1 gene on chromosome 14. Neuropathologic examination of the husband's brain showed neuritic and diffuse "cotton-wool" plaques together with meningovascular and parenchymal amyloid angiopathy involving cerebral and cerebellar cortex (CERAD D; BRAAK VI) and severe periventricular leukoaraiosis (Abstract 173 figure 2 ). Family history through seven generations revealed individuals in every generation to have a phenotype similar to the index case. The typical clinical and pathological features of the Presenilin 1 Glu280Gly mutation may mimic more common neurodegenerative or neuroinflammatory diseases. In patients presenting with limb spasticity and cognitive impairment Presenilin 1 mutations should be considered in the differential diagnosis.